2-Substituted furans from Polyalthia suberosa - P. Tuchinda (2018)
Two new 2-substituted furans, 1-(2-furyl)pentacosa-16,18-diyne and 23-(2-furyl)tricosa-5,7-diynoic acid, have been isolated from stems of Polyalthia suberosa. The structures were assigned by spectroscopic methods. The two compounds together with the previously reported kalasinamide, N-trans-feruloyltyramine and N-trans-coumaroyltyramine showed anti-HIV activities.